Pengaruh Transformasi Digital dan Learning Organization Terhadap Motivasi Kerja ASN di Balai Veteriner Lampung - Budiyah Budiyah; Hendri Dunan (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
In response to increasing demands for fast, effective, efficient, and transparent public services, the Lampung Veterinary Center, as an animal disease laboratory, has implemented digital transformation through the utilization of data-driven technologies, automation systems, and digital integration. The success of this transformation requires the organization’s ability to continuously learn and adapt to change, commonly referred to as a learning organization. However, pressure to meet service demands within a relatively short time frame, combined with the requirement to continuously learn and adapt, may increase workload and work-related stress among civil servants if not supported by adequate systems, human resource capacity development, and a conducive work environment. These conditions may ultimately affect employees’ work motivation. This study aims to analyze the effect of digital transformation on the work motivation of civil servants at the Lampung Veterinary Center, to examine the effect of a learning organization on work motivation, and to assess the simultaneous effect of digital transformation and learning organization on work motivation. This study employs a quantitative approach using multiple linear regression analysis. The results show that digital transformation has a positive and significant effect on the work motivation of civil servants at the Lampung Veterinary Center, learning organization has a positive and significant effect on work motivation, and digital transformation and learning organization simultaneously have a positive and significant effect on the work motivation of civil servants.